Implementation of Extension Curricularization in the Medical Course: The Integrative Week Model (CIPEEX, 2025)
In 2014, the Ministry of Education launched the challenge of curricularizing extension, requiring that 10% of the course workload be developed in the community. Several medical education forums have debated how to make it feasible to implement this significant extension workload in the community for all students of each term, in a curricular manner. This paper aims to report the experience of the medical course in implementing extension curricularization. After a series of meetings, the Structuring Teaching Core (NDE) of the medical course decided to establish an “Integrative Week” in the community. During this week, students visit community settings and carry out health education actions, basic guidance acquired in the classroom, integrating different areas of knowledge learned in the semester, all under faculty supervision. The health promotion workshops are designed to align with classroom learning, connecting teaching and extension. Currently, six cohorts are involved in the integrative week, comprising around 600 students. Several workshops have been developed for children, adolescents, adults, and the elderly. Partnerships were established with municipal and state schools, senior day centers, the Open University for the Elderly (UNIAPI), and local industries. Various initial challenges were faced, one of the most difficult being the effective participation of faculty, including their availability to travel to the community setting. Another challenge was organizing a large number of students working in the same setting. It is concluded that extension curricularization was effective in improving students’ knowledge and in promoting health within the community.
Keywords: curricularization; extension; medical education